MALAKOPLAKIA OF THE URINARY BLADDER - A CASE REPORT - Ali, Zafar; Farouk, Khalid; Khan, Muhammad Ayaz; Hanif, Shumaila; Javed, Jabran (Journal of Postgraduate Medical Institute, 2011)
Malakoplakia is a chronic inflammatory condition presenting as a plaque or a nodule affecting the genitourinary tract. Malakoplakia was first documented in the 1900s as yellow soft plaques seen on the mucosa of the urinary bladder.